A model for effective national housing fund in Nigeria - Oluwatosin, Adediran Anthonia (2021)
The housing sector and homeownership are characterized by a number of benefits which have significant impacts on human lives and economic growth. Effective housing finance system, therefore, plays a key role in assuring the realization of such benefits. Despite the existence of successful housing finance models across countries, Nigeria housing finance system is yet to have a model that supports the operation of government initiated National Housing Fund Scheme, a source of housing mortgages for the public servants and private housing developers. To put it succinctly, housing finance in Nigeria has been ineffective, while workable policies appear to be a long way off the entire policy. This study seeks to fill this gap by developing a model for an effective National Housing Fund Scheme to aid homeownership in the country. This study has three objectives: 1) to identify the constraints affecting National Housing Fund Scheme loan transactions; 2) to develop a model and action plan for effective national housing fund in Nigeria through identified indicators, and 3) to validate the implementation model for effective national housing fund in Nigeria. In accomplishing the research goal, four stages of survey were performed. In Stage 1, interviews were conducted with housing related professionals, academics and mortgage institution officials; in Stage 2, four hundred and fifteen questionnaires were administered among public workers across the southwest of Nigeria; in Stage 3, a two-stage FGD was conducted involving fourteen individuals consisting of housing related professionals, academics, public servants and housing finance experts, and in Stage 4, a questionnaire survey on model validations was carried out with twenty-seven housing experts. SPSS, Structural Equation Model and NVivo were used to analyse the obtained data. The results show that the facilitation of effective National Housing Fund Scheme in Nigeria falls under three categories namely Macro-economic operations, Micro-economic operation and Action Plan, which were then pooled together to develop a model for effective National Housing Fund. A pool of experts unanimously gave their support to the appropriateness, validity and easy comprehension of the model, suggesting its validity. The capacity of the Model in providing guides to all stakeholders on housing mortgage transactions was also confirmed. Based on the findings, the dual stages of effective National Housing Fund Model are essential in enabling concerned individuals or groups to better understand their roles in Housing Finance Originations and subsequent transactions towards stakeholders’ homeownership.